2013
DOI: 10.1007/s00167-013-2553-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of all-inside meniscal repair

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 27 publications
3
76
2
4
Order By: Relevance
“…The present study found a protective effect of repair against osteoarthritis, in agreement with the literature: long-term cartilage degradation rates range from 8% to 43% after repair, versus 21% to 64% after meniscectomy [8,10,20,23,24,[28][29][30][31]33,35,36]: i.e., a factor of 2. Table 2 Correlation between functional and quantitative radiological scores, both groups taken together.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found a protective effect of repair against osteoarthritis, in agreement with the literature: long-term cartilage degradation rates range from 8% to 43% after repair, versus 21% to 64% after meniscectomy [8,10,20,23,24,[28][29][30][31]33,35,36]: i.e., a factor of 2. Table 2 Correlation between functional and quantitative radiological scores, both groups taken together.…”
Section: Discussionsupporting
confidence: 92%
“…There are numerous reports of results in meniscectomy [2][3][4][5][6][7][8]10,[22][23][24] and meniscal repair [25][26][27][28][29], comparisons between the two [20,30,31] and meta-analyses [32][33][34]. Interpretation, however, is hindered by numerous biases: meniscal surgery was either isolated or associated to anterior cruciate ligament surgery; patient ages and clinical and radiological assessment scoring systems differed; follow-up was short or variable; and initial meniscal lesion type, repair technique, meniscectomy extent and initial chondral status were not always specified.…”
Section: Discussionmentioning
confidence: 99%
“…These end points may be discordant, in part because partially healed menisci may or may not be symptomatic. 122 MR imaging findings After a repair procedure, the meniscus can be categorized as healed if there is no fluid signal in the repair, partially healed if fluid signal extends into less than 50% of the repair site, or not healed if fluid signal extends into greater than 50% of the repair site (Figs. 20 and 21).…”
Section: Repair Outcomesmentioning
confidence: 99%
“…Meniscus repair with sutures or suture anchor systems represents the gold standard treatment especially in the young and active patient [4,23]. However, meniscal repair…”
Section: Introductionmentioning
confidence: 99%